Structure and distribution of the collembula fauna of Khurush high-mountainous hills - G. M. Abdurakhmanov; M. M. Ajtekova (Юг России: экология, развитие)
The information about the solution and biotopic allocation of the collembula fauna of South Dagestan Alpine depending on the structure, chemism of the soil and plants are considered in the article.